Towards an aesthetic of intimacy. A contribution to the critique of Mikel Dufrenne - Morais, Carlos Bizarro (2021)
Across the works of Mikel Dufrenne, the category of intimacy occurs almost always as a way to heighten the attributes of reciprocity, sharing, close friendship and communion of feelings which shape the bond between spectator and aesthetical object or artwork at the core of the aesthetic experience. In this sense, intimacy is a reticular concept, interchangeable with “profoundness”, “interiority”, “connaturality”. Hence, the aesthetic experience is, in a way, a zenith of intimacy, a paradigm of “intimate life”, namely, the moment where spectator, artist and the work disrobe and reveal themselves – in other words, when they mutually share the complicit removal of the veils concealing them. However, contrary to what such openness could suggest, the intimacy experienced herein does not designate a secret event, not even a private slice of the above actors’ hidden life. Intimacy is not placed in the domain of “intimism”, of particular affection, which a certain psychoanalysis tends to highlight. Converting intimacy into a pretext or grounds for a clinic, psychoanalytic function is of no interest to Mikel Dufrenne, as it corrupts the very aesthetic process. In this interpretative context, we intend, first and foremost, to consider the theoretical implications of Mikel Dufrenne’s proposal about the theme of intimacy. We also intend to demonstrate that, by shielding the category of intimacy from the quite frequent risks of instrumentalisation, intimacy becomes available to assist in renovating the meaning of overarching phenomenological themes, such as intentionality and constitution. We also aim at illustrating how the aesthetic experience is a naturally intimate relationship, bestowing it with an ontological dimension from the very beginning. Following on this interpretation, quite beyond what the author made explicit, we wish to contribute to the proper critical appraisal of the thought of one of the greatest aesthetic philosophers - Mikel Dufrenne.